1997
DOI: 10.1029/96pa03120
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary high‐resolution biomarker and other sedimentary climate proxies in a Northeast Atlantic Core

Abstract: Abstract. We studied variations in terrigenous input and sea surface temperature over the last 208 ka using a multiproxy approach, involving direct comparison of terrigenous and marine molecular biomarker, foraminiferal abundance, and other sedimentological data for the same horizons in a single northeast Atlantic core (core T88-9P; 48o23 ' N, 25o05 ' W, 3193 m water depth, 790 cm core length) with a well-resolved •5180 stratigraphy. The abundances of three landderived, long-chain compound classes, the n-alkan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 63 publications
2
35
2
5
Order By: Relevance
“…The presence of extensive loess deposits between 45 and 35°N in the interior of North America (Bettis et al, 2003) indicates that the margins of the North American ice sheets were a major dust source during the last glacial, in-line with modeling results (Ganopolski et al, 2010). Studies using the accumulation of organic biomarkers derived from terrestrial higher plant leaf waxes in marine sediments from the northern North Atlantic, downwind from the North American continent, demonstrate similar results with increased aeolian input of terrestrial material during the last glacial (López-Martínez et al, 2006;Madureira et al, 1997).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The presence of extensive loess deposits between 45 and 35°N in the interior of North America (Bettis et al, 2003) indicates that the margins of the North American ice sheets were a major dust source during the last glacial, in-line with modeling results (Ganopolski et al, 2010). Studies using the accumulation of organic biomarkers derived from terrestrial higher plant leaf waxes in marine sediments from the northern North Atlantic, downwind from the North American continent, demonstrate similar results with increased aeolian input of terrestrial material during the last glacial (López-Martínez et al, 2006;Madureira et al, 1997).…”
Section: Introductionsupporting
confidence: 61%
“…They are a major component of modern dust even in remote ocean areas (Conte and Weber, 2002;Conte et al, 2003;Gagosian et al, 1981;Simoneit et al, 1977) as they can easily be removed from the leaf surface by wind or rain, especially by sandblasting during dust storms, or entrained as part of soil and transported over large distances. Numerous studies therefore used the accumulation of these lipids in distal marine sediments far from major fluvial inputs to infer changes in aeolian input to the open ocean (e.g., López-Martínez et al, 2006;Madureira et al, 1997;Martínez-Garcia et al, 2009. Indeed, several studies have shown that the concentrations and fluxes of these organic biomarkers agree well with those of independent inorganic tracers for windborne lithogenic material (e.g.…”
Section: Accumulation Rates Of N-alkanes and N-alkan-1-olsmentioning
confidence: 80%
“…21,22 These compounds are abundant in plant epicuticular waxes, 23 but long-chain n-alkanes and n-alkanoic acids can also be found in marine algae. [24][25][26] …”
Section: Introductionmentioning
confidence: 99%
“…Os trabalhos enfocam, por exemplo, a importância que o registro quantitativo dos compostos orgânicos (normalmente denominados de biomarcadores) tem para estudos sobre produtividade primária (biomassa de fitoplâncton), fluxo de material terrestre, mudanças climáticas e presença de poluentes [5][6][7][8][9] . Entretanto, devido ao alto custo dos cruzeiros científicos que são necessários para os trabalhos em oceanos e pela própria dificuldade de se coletar amostras em regiões onde a coluna d'água pode atingir mais de 4000 m de profundidade, poucos trabalhos têm examinado a composição lipídica da matéria orgânica presente em sedimentos abissais, particularmente no Oceano Atlântico [10][11][12] . O presente trabalho foi desenvolvido como parte do projeto britânico BOFS (do inglês "Biogeochemical Ocean Flux Study ", 1990 -1994), que tinha como objetivo avaliar o ciclo do carbono orgânico no Atlântico Norte, sendo, portanto, uma ótima oportunidade para se identificar alguns dos grupos de compostos orgânicos encontrados em sedimentos oceânicos.…”
Section: Introductionunclassified